Informal housing and property tax - Marquez Valdez, Joaquin Ernesto (2022)
This article seeks to clarify the positive relationship between the inclusion of informal organizations under a registry that allows the collection of property tax in response to assistance in the delivery of proof of possession for access to basic services. The methodology has been carried out under a non-experimental and descriptive investigation, which has shown a lack of state capacities to prevent invasions. In addition, there is a weakness in the tax collection capacity for a private group already titled and registered, so an attempt is made to solve a social problem alleging the need, but without a planned municipal management that can mitigate basic care such as health, safety and others. from effective tax collection. The figure of the passive subject of the property tax is adjusted to a literal interpretation. However, reality shows that there is an important and considerable mass that lives under a situation of possession. The conclusions show that passivity in the collection approach will generate greater damage in the future, since it has been shown that the absence already established both in the inspection and in the restriction of invasions has led to these actions being maintained and prospering.